Role of synergy and immunostimulation in design of chemotherapy combinations: An analysis of doxorubicin and camptothecin - Anusha Pusuluri; Vinu Krishnan; Debra Wu; C. Wyatt Shields IV; Li W. Wang; Samir Mitragotri (Wiley, 2019)
Abstract Combination chemotherapy is often employed to improve therapeutic efficacies of drugs. However, traditional combination regimens often utilize drugs at or near‐their maximum tolerated doses (MTDs), elevating the risk of dose‐related toxicity and impeding their clinical success. Further, high doses of adjuvant or neoadjuvant chemotherapies can cause myeloablation, which compromises the immune response and hinders the efficacy of chemotherapy as well as accompanying treatments such as immunotherapy. Clinical outcomes can be improved if chemotherapy combinations are designed to reduce the overall doses without compromising their therapeutic efficacy. To this end, we investigated a combination of camptothecin (CPT) with doxorubicin (DOX) as a low‐dose treatment option for breast cancer. DOX‐CPT combinations were synergistic in several breast cancer cell lines in vitro and one particular ratio displayed extremely high synergy on human triple negative breast cancer cells (MDA‐MB‐231). This combination led to excellent long‐term survival of mice bearing MDA‐MB‐231 tumors at doses roughly five‐fold lower than the reported MTD values of its constituent drugs. Impact of low dose DOX‐CPT treatment on local tumor immune environment was assessed in immunocompetent mice bearing breast cancer (4T1) tumors. The combination was not only superior in inhibiting the disease progression compared to individual drugs, but it also generated a more favorable antitumor immunogenic response. Engineering DOX and CPT ratios to manifest synergy enables treatment at doses much lower than their MTDs, which could ultimately facilitate their translation into the clinic as a promising combination for breast cancer treatment.